Comparison of Gastrointestinal Symptoms and Disease Severity in COVID-19 Patients - Umbreen Aslam, Muhammad Kashif Bashir, Nosheen Zafar, Niamat Ali, Shazia Siddique, Nida Basheer (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In COVID 19 patients, before the onset of respiratory distress, GI symptoms occur earlier. GI Symptoms are common, and in many patients the first symptoms are diarrhea or vomiting rather than respiratory problems. The aim of current study was to find out the most common GI symptoms and its effect on disease severity. Methods: A cross sectional study was conducted at Sir Gaga Ram Hospital Lahore from March to April 2020 at Corona Isolation Wards. Total 150 covid-19 polymerase chain reaction (PCR) positive patients were enrolled. Patients were keenly observed for symptoms and all the symptomatic patients were enrolled in study. Patient’s demographic data and presenting complaints were recorded on predesigned Performa. Data was enter and analyzed by using SPSS 21.0. Association between disease severity and GI was determined by using Chi-square test. P-value <0.05 was considered as significant. Results: Total 150 patients were enrolled in current study. The mean age of patients were in mild group were 37+15 and moderate severity group were 41+18. There were 58(44.2%) male in mild and 10(52.6%) in moderate group. There were 73(55.7%) female in mild and 9(47.3%) in moderate group. Most common respiratory symptoms was anosmia 65(43.3%), followed by cough 47(31.39) and sore throat 31(20.7%). Most common gastrointestinal symptoms was Diarrhea 49(32.7%) and nausea 48(57.9%). Nausea was present in 37(28.2%) mild cases and 11(57.9%) in moderate cases. The significant association was observed between disease severity and abdominal pain, nausea. Conclusion: Majority of patients with COVID-19 presents with both respiratory and gastrointestinal symptoms. Patients with mild to moderate severity of disease have diarrhea and nausea the most common GI symptoms. GI Symptoms are common, and in many patients rather than respiratory distress in early onset. Keywords: COVID-19, Gastrointestinal symptoms, Disease severity